Consultations for clinical features of possible cancer and associated urgent referrals before and during the COVID-19 pandemic: an observational cohort study from English primary care - Nicholson, B; Ordonez-Mena, J; Sheppard, J; Smith, M; Williams, J; Wright Drakesmith, C; Perera, R; De Lusignan, S; Hobbs, F; Bankhead, C (Springer Nature, 2021)
BACKGROUND: It remains unclear to what extent reductions in urgent referrals for suspected cancer during the COVID-19 pandemic were the result of fewer patients attending primary care compared to GPs referring fewer patients.